Gamitaeeumjowee-tang for Overweight and Obese Patients with Gastroesophageal Reflux Symptoms: A Retrospective Chart Review - Ji-Min Kim; Min-Jeong Kim; Seo-Young Kim; Ka-Hye Choi (Journal of Korean Medicine, 2026)
Objectives: This study evaluated the weight loss outcomes and gastrointestinal safety profile of Gamitaeeumjowee-tang in overweight and obese patients with gastroesophageal reflux symptoms and examined the association between adverse events (AEs) and both medication adherence and treatment outcomes.Methods: A retrospective chart review was conducted on 58 patients (mean age, 40.47±11.60 years) with a body mass index (BMI) ≥ 23kg/m² and self-reported gastroesophageal reflux symptoms who completed a 12-week weight loss program. Participants received Gamitaeeumjowee-tang tablets (containing 16–24 g of Ephedra sinica/day, three times daily). Changes in body weight, BMI, waist-to-hip ratio (WHR), and visceral fat area (VFA) were assessed.Results: The mean weight loss was 5.81±2.40 kg, with a significant reduction in BMI, WHR, and VFA (P < 0.001). A total of 86.2% of patients achieved ≥ 5% weight loss. AEs occurred in 67.0% of participants, mostly during the first six weeks; most were mild (92.7%) and considered unlikely related to medication (70.9%). Gastrointestinal symptoms were the most common AEs, but typical gastroesophageal reflux symptoms (heartburn and regurgitation) were rare (1.8%–5.7%). There were no significant differences in weight loss or medication adherence based on the presence or type of AEs, including upper gastrointestinal or gastroesophageal reflux symptoms.Conclusions: Gamitaeeumjowee-tang was associated with weight reduction in overweight and obese patients with gastroesophageal reflux symptoms. Despite concerns regarding the gastrointestinal adverse effects of weight-loss medications, typical gastroesophageal reflux related AEs were infrequent and mostly mild, without reducing medication adherence or treatment outcomes.